A CREATOR IN THE AGE OF THE INTERNET BASED ON THE EXAMPLES OF POLISH E-LITERATURE - Winiecka, Elżbieta (Porównania, 2019)
The article presents transformations of the artist’s myths in electronic literature. The subject of research is the space of the Internet and literary phenomena developing with the use of digital tools. The authoress searches for the answer to the question whether and how the literary myths of the artist, derived from modernism, appear in the new technological and cultural as well as communication reality, and what new patterns of authorship appear in their place. The attitudes, observed over the last dozen or so years, have been described in the Polish Internet space on the example of the author and theoretician Zenon Fajfer, the cyberpoet and philosopher Roman Bromboszcz, as well as two group projects: the Hub of Rozdzielczość Chleba Publishing House (whose activity ended in October 2018) and Pixel Zdrój initiated and coordinated by Mariusz Pisarski. The sketch has the character of preliminary findings, which – also due to the nature of the online medium – must be subject to further modifications.